Textbook of palliative care communication - Wittenberg, Elaine (Oxford University Press, 2016)
'The Textbook of Palliative Care Communication' is the authoritative text on communication in palliative care. Uniquely developed by an interdisciplinary editorial team to address an array of providers including physicians, nurses, social workers, and chaplains, it unites clinicians and academic researchers interested in the study of communication.